Disentangling demographic effects of red deer on chamois population dynamics. Issue 12 (25th May 2021) - Donini, Valerio; Pedrotti, Luca; Ferretti, Francesco; Corlatti, Luca
Abstract: Investigating the impact of ecological factors on sex‐ and age‐specific vital rates is essential to understand animal population dynamics and detect the potential for interactions between sympatric species. We used block count data and autoregressive linear models to investigate variation in birth rate, kid survival, female survival, and male survival in a population of Alpine chamois Rupicapra rupicapra rupicapra monitored over 27 years within the Stelvio National Park, Central Italian Alps, as function of climatic variables, density dependence, and interspecific competition with red deer Cervus elaphus . We also used path analysis to assess the indirect effect of deer abundance on chamois growth rate mediated by each demographic parameter. Based on previous findings, we predicted that birth rate at [ t ] would negatively relate to red deer abundance at year [ t − 1]; survival rates between [ t ] and [ t + 1] would negatively relate to red deer abundance at year [ t − 1] and to the interactive effect of winter precipitation at [ t + 1] and chamois density at [ t ]. Our results showed that birth rate was positively related to spring–summer precipitation in the previous year, but this effect was hampered by increasing red deer abundance. Kid and female survival rates were negatively related to the combined effect of chamois abundance and winter precipitation. Male and female survival rates were negatively related to lagged red deer abundance. The path analysis supported a negative indirect effect of red deer abundance on chamois growth rate mediated by birth rate and female survival. Our results suggest that chamois population dynamics was largely explained by the synergistic effect of density dependence and winter harshness, as well as by interspecific competition with red deer, whose effects were seemingly stronger on the kid–female segment of the population. Abstract : Understanding variation in key life‐history traits requires to disentangle the impact of ecological variables on sex‐ and age‐specific vital rates. Red deer Cervus elaphus can act as a potential competitor to the chamois Rupicapra rupicapra, hampering population growth rate. Our results support a strong negative effect of red deer abundance on chamois demographic parameters, thereby supporting the role of interspecific competition, especially on the kid–female segment of the population. ​